Ankle-brachial index and brachial-ankle pulse wave velocity are associated with albuminuria in community-based Han Chinese. (2nd October 2016) - Xu, Xiqi; He, Jinggui; Wang, Shuxia; Zhu, Ping; Chen, Qian; Zhang, Xiujin; Tao, Tao; Wang, Hao; Liu, Jianfeng; Wang, Haijun; Li, Xiaoying
ABSTRACT: Background/objectives : Our study aimed to explore whether the ankle-brachial index (ABI) and brachial-ankle pulse wave velocity (baPWV) were associated with albuminuria in community-based Han Chinese. Methods : Total 2127 subjects (860 men and 1267 women) aged 60 years and over were recruited in Beijing. Albuminuria was assessed by the urinary albumin-to-creatinine ratio (UACR) of ≥30 mg/g. BaPWV was divided by quartile. The logistic regression was used to determine the odds ratio (OR) and 95% confidence intervals (CIs) of ABI and baPWV with albuminuria. Results : ABI was associated with albuminuria in the interaction model (OR 0.89, 95% CI 0.81–0.99 by every 0.1 unit increase of ABI), especially in hypertension (OR 0.82, 95% CI 0.73–0.92) and diabetes (OR 0.83, 95% CI 0.68–0.98) groups. BaPWV groups were also significantly associated with albuminuria, ORs of having albuminuria for baPWV quartile II, III, and IV were 1.02(0.65–1.52), 1.05(0.72–1.61), and 1.18(1.04–1.47) in the interaction model. For hypertension and diabetes patients, only the baPWV quartile IV group had higher OR. Conclusions : ABI and baPWV were associated with albuminuria after adjusting for other risk factors in Chinese community-based elderly Han population. The association of ABI with albuminuria was stronger in hypertension and diabetes patients.